Novel Frameshift Heterozygous Mutation in UBAP1 Gene Causing Spastic Paraplegia-80: Case Report With Literature Review - Zhang, Chao; Zhu, Xiaowei; Zhu, Zeyu; Ni, Ruilong; Liu, Taotao; Zheng, Haoran; Liu, Shihua; Cao, Li; Zhong, Ping; Tian, Wotu (Frontiers in Neurology, 2022)
Hereditary spastic paraplegia (HSP) represents a group of rare inherited neurodegenerative conditions, characterizes by progressive lower limb spasticity. Ubiquitin-associated protein 1 (UBAP1)-related-HSP is classified as Spastic paraplegia 80 (SPG80), which is an autosomal dominant (AD) juvenile-onset neurologic disorder and mainly affects the lower limbs. We described the clinical and genetic features of two patients within the same family caused by a heterozygous mutation of the UBAP1 gene. The proband was a 34-year-old woman with progressive spasticity and hyperreflexia in the lower limbs for 26 years. Her mother also had similar symptoms since the age of 6. The proband and her mother only had motor dysfunction, such as unsteady gait, hypertonia and hyperreflexia of lower limbs. Other system functions (sensory, urinary, visual, and cognitive impairment) were not involved. WES disclosed a frameshift mutation (c.371dupT) in UBAP1 gene, which was predicted to be ‘likely pathogenic’ and was co-segregated in the pedigree. c.371dupT, encoding the truncated UBAP1 protein with 72.6% missing of the normal amino acid sequence, is responsible for this family with spastic paraplegia (SPG). In combination with the clinical characteristics, genetic testing results and co-segregation analysis, the diagnosis is considered to be pure Spastic paraplegia-80 (SPG80), which is an autosomal dominant disease. By retrospectively analyzing the documented cases, we comprehensively review the phenotypic features and summarize the genotype spectrum of SPG80 to enhance earlier recognition and therapeutic strategies.